The Analysis of β-cryptoxanthin and Zeaxanthin using HPLC in the Accumulation of Orange Color on Lowland Citrus - Inanpi Hidayati Sumiasih; Roedhy Poerwanto; Darda Efendi; Andria Agusta; Sri Yuliani (Hasanuddin University, 2017)
Citrus peel color is one of the main quality attributes which was caused by the accumulation of carotenoids and its derivatives, especially β-citraurine. It makes citrus peel color looks attractive (orange). The orange color is a mixture of β-cryptoxanthin with β-citraurin. The objectives of this study were (1) to observe the effect of precooling and duration of proper ethylene exposure in the formation of orange color on citrus peel, (2) to identify and determine the β-cryptoxanthin content and total chlorophyll on citrus peel. Citrus was from Tuban, East Java while the study was conducted at PKHT IPB and LIPI. Precooling and without precooling treatment prior to injection of 100 ppm of ethylene exposed at 15 °C, duration of exposure control (0), 24, and 48 hours. The results show that the best color of the Citrus Color Index (CCI) is the precooling treatment and the duration of ethylene exposure for 24 hours, which can reduce total chlorophyll content about 8 times and proved to increase β-cryptoxanthin pigment content five times in accelerating the formation of orange citrus reticulata peel color to bright orange. Degreening has no significant effect on total dissolved solids and the firmness level of citrus fruits.Keyword: β-cryptoxhantin; citrus; chlorophyll; degreening; ethylene zeaxanthin.